2012
DOI: 10.1128/jb.01314-12
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Desulfurococcus fermentans, a Hyperthermophilic Cellulolytic Crenarchaeon Isolated from a Freshwater Hot Spring in Kamchatka, Russia

Abstract: Desulfurococcus fermentans is the first known cellulolytic archaeon. This hyperthermophilic and strictly anaerobic crenarchaeon produces hydrogen from fermentation of various carbohydrates and peptides without inhibition by accumulating hydrogen. The complete genome sequence reported here suggested that D. fermentans employs membrane-bound hydrogenases and novel glycohydrolases for hydrogen production from cellulose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 6 publications
(6 reference statements)
0
11
0
Order By: Relevance
“…The 16S rRNA gene sequences of D. amylolyticus Z-533 T differ by 0.1 to 0.3% from those of other D. amylolyticus strains, namely, Z-1312 and 1221n (24), which were formerly known as D. fermentans Z-1312 and D. kamchatkensis 1221n, respectively (5). Of these, only D. amylolyticus Z-1312 degrades cellulose (2) and is not inhibited by the presence of hydrogen (6).…”
Section: Genome Announcementmentioning
confidence: 92%
“…The 16S rRNA gene sequences of D. amylolyticus Z-533 T differ by 0.1 to 0.3% from those of other D. amylolyticus strains, namely, Z-1312 and 1221n (24), which were formerly known as D. fermentans Z-1312 and D. kamchatkensis 1221n, respectively (5). Of these, only D. amylolyticus Z-1312 degrades cellulose (2) and is not inhibited by the presence of hydrogen (6).…”
Section: Genome Announcementmentioning
confidence: 92%
“…As for the Crenarchaeota, our current knowledge is restricted to two publications that report a relatively weak growth on cellulose for representatives of Desulfurococcales (Perevalova et al, 2005;Kochetkova et al, 2016). Surprisingly, in the genomes of these archaea, no genes of known cellulase families were found that hide their cellulose hydrolysis mechanisms (Mardanov et al, 2012;Susanti et al, 2012). On the other hand, cellulase genes were found in the genomes of some other crenarchaeota, for which the growth on cellulose was not shown.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these kinds of biocatalysts are noticeable and confident templates for protein engineering purposes. There are several reports regarding isolation of thermophilic bacteria and fungi and the characterization of their endoglucanase activity ( Bhalla et al ., 2013 ; Hreggvidsson et al ., 1996 ; Karnaouri et al ., 2014 ; Mead et al ., 2012 ; Susanti et al ., 2012 ). The importance of thermophilic bacteria and their thermostable enzymes to overcome the bottlenecks of existing processes of lignocellulosic biomass conversion, the effect of high temperatures on bioprocessing of saccharification and fermentation, and the new trends in improved lignocellulosic conversion to bioethanol have also been discussed ( Bhalla et al ., 2013 ; Li D-C et al ., 2011 ).…”
Section: Introductionmentioning
confidence: 99%